The diagnostic performance of the one-step nucleic acid amplification assay for the detection of sentinel lymph node metastases in cytokeratin 19-positive breast cancer: a PRISMA-compliant meta-analysis - Liu, Meirong; Wang, Weihua; Wang, Yufang (Frontiers in Medicine, 2024)
The status of the sentinel lymph nodes (SLNs) was an important prognostic factor for many different types of cancer. The one-step nucleic acid amplification (OSNA) assay has emerged as a rapid intraoperative molecular diagnostic tool for lymph node metastasis detection. We aimed to evaluate and summarize the value of OSNA assay for the diagnosis of sentinel lymph node metastasis in cytokeratin 19-positive breast cancer.Methods: To evaluate the diagnostic value, the sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and area under the curve (AUC) were pooled. Threshold effect followed by subgroup analysis was performed to explore the source of heterogeneity. Sensitivity analysis was performed to assess the stability of this meta-analysis model. Fagan plots and likelihood ratio scattergrams were used to explore the potential clinical significance.Results: Twenty-nine eligible studies which consisted of 5331 patients with 10343 sentinel lymph nodes were included in this meta-analysis. The pooled sensitivity, specificity, PLR, NLR, and DOR were 0.86 (95% CI: 0.85-0.88), 0.94 (95% CI, 0.94-0.95), 18.00 (95% CI, 13.54-23.92), 0.13 (95% CI, 0.10-0.17), and 138.99 (95% CI, 86.66-222.92), respectively. The AUC was 0.97 (95% CI, 0.95-0.98). Sensitivity analysis showed that four studies had an impact on the pooled results and mainly contributed to the heterogeneity. Fagan's nomogram revealed that the prior probability of 50%, the post probability positive, the post probability negative were 95% and 11%, respectively. Discussion: Our results suggested that OSNA can predict the occurrence of SLN metastasis in CK19-positive breast cancer. However, more well-designed and multicenter diagnostic tests are needed to validate our results.